2017
DOI: 10.1160/th17-07-0478
|View full text |Cite
|
Sign up to set email alerts
|

Long-term bleeding risk prediction in ‘real world’ patients with atrial fibrillation: Comparison of the HAS-BLED and ABC-Bleeding risk scores

Abstract: Risk scores in patients with atrial fibrillation (AF) based on clinical factors alone generally have only modest predictive value for predicting high risk patients that sustain events. Biomarkers might be an attractive prognostic tool to improve bleeding risk prediction. The new ABC-Bleeding score performed better than HAS-BLED score in a clinical trial cohort but has not been externally validated. The aim of this study was to analyze the predictive performance of the ABC-Bleeding score compared to HAS-BLED sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 49 publications
(45 reference statements)
0
12
0
1
Order By: Relevance
“…Finally, our newly constructed nomogram model included a wide range of clinical risk factors, namely, age at diagnosis, race, EOD, tumor size, and surgery, which were easily available and routinely collected from historical records. Figure 4 shows the results of our DCA, wherein the abscissa and ordinate are the threshold probability and net benefit rate, respectively [2831]. To the best of our knowledge, this study is the first to use IDI, NRI, and DCA in the verification of the predictive abilities of nomograms for ES.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our newly constructed nomogram model included a wide range of clinical risk factors, namely, age at diagnosis, race, EOD, tumor size, and surgery, which were easily available and routinely collected from historical records. Figure 4 shows the results of our DCA, wherein the abscissa and ordinate are the threshold probability and net benefit rate, respectively [2831]. To the best of our knowledge, this study is the first to use IDI, NRI, and DCA in the verification of the predictive abilities of nomograms for ES.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the results of DCAs, with the abscissa corresponding to the threshold probability and the ordinate being the net benefit rate. [ 34 36 ] The figure illustrates that the new model yielded net benefits that were superior to those of the traditional AJCC staging system. These results together demonstrate that our nomogram would provide useful information about the risks and benefits of certain treatment plans, thereby helping clinicians to make good decisions and even provide psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world studies investigating the usefulness of sequential addition of biomarkers have shown limited value over conventional clinical risk scores. 10 , 308 , 309 Thus, statistically significant improved prediction should not be confused with clinically improved risk prediction. A balance is therefore needed between (statistically) improved risk prediction and simplicity or practicality for everyday clinical use in busy clinical settings.…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Atrmentioning
confidence: 99%